Caquetá: región sin ley, territorio sin bosques (2020)
In the last two decades, deforestation in the Amazon Forest has become an important topic due to its negative environmental and social impacts. During this time, researchers have studied deforestation in countries that share the Amazon Basin, but there's still not strong literature about the Colombian Amazon. In this research, I use panel data to understand the how deforestation in selected cattle-ranching properties is linked to their access to roads. I also take into account the institutional changes due to the 2016 Peace Treaty, capturing the effect of roads in deforestation since 2016. I find that, after 2016, deforestation in land properties decreases if they are closer to roads and if these are paved. Also, coca crops seem not to have a clear link to deforestation.